EL “HABLANTE NATIVO” DE LA LENGUA META: ¿QUÉ IMPORTANCIA TIENE PARA LA ENSEÑANZA DE LA L2? - Chacón Beltrán, Rubén (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper centers on research related to a concept used very often in the field of foreign language learning and teaching: the belief that native speaker usage is the definite standard of the target language. Too frequently we use it as the ultimate criterion for language correctness and/or appropriateness, especially in the L2 classroom. My goals were to identify some skills ideally attributed to the native speaker, to test them with empirical research and to check their validity. In this paper I deconstruct some of the abilities linguists have traditionally attributed to the native speaker of any language; specifically, I examine the ability to produce fluent spontaneous written discourse. I was able to validate my hypothesis that native speaker’s individal variation accounts for its inadecuacy as a justification for L2 learners’ performance in L2 tests. Finally, I infer some pedagogical implications teachers will need to take into account when evaluating writing achievements in the L2.